2020
DOI: 10.1017/s2045796020000360
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent depression and subsequent earnings across early to middle adulthood: a 25-year longitudinal cohort study

Abstract: Aims The few available studies on early-onset depression and future earnings offer ambiguous findings, and potential sources of heterogeneity are poorly understood. We examined the differences in adult earnings of males and females with and without a history of depressive disorder in adolescence, with specific focuses on (1) future earnings in clinical subtypes of adolescent depression; (2) the growth and distribution of earnings over time within these subgroups and (3) the mediating role of subsequent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…Adjustment for several time-varying background variables such as educational level, marital status and motherhood did not alter this. Our results are in accordance with previous research showing that mental disorders are associated with subsequent income loss [23][24][25][26]. Furthermore, we also found the effect of mental disorders, de ned by OPMH treatment, to vary by income level, with greater adverse effects among women in the low-income group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adjustment for several time-varying background variables such as educational level, marital status and motherhood did not alter this. Our results are in accordance with previous research showing that mental disorders are associated with subsequent income loss [23][24][25][26]. Furthermore, we also found the effect of mental disorders, de ned by OPMH treatment, to vary by income level, with greater adverse effects among women in the low-income group.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found that mental disorders have a negative impact on several work-related outcomes such as poor labour market attachment [19][20][21][22] and lower earnings, with an income reduction of between 6.5 and 20.0 percent [23][24][25][26]. This loss of income has been explained by reduced productivity or concentration.…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, early exposure to depression or depression symptoms may also interfere with normal development in other important life domains, such as school performance (e.g., GPA) [64] and attainment of tertiary education [3], which are important factors in the context of labor market outcomes [13]. While previous research has indicated that educational attainment [16] and recurring bouts of depression [16,20] may play an intermediate role in determining adult socioeconomic outcome, there has been no study to date addressing the risk of marginalization from the labor market while accounting for various sources of important heterogeneity associated with adolescent depression and its longer-term outcomes. In the present study, we sought to expand on the preliminary evidence pointing to the roles played by both the educational paths taken and the illness course of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms affect several labour market outcomes, including NEET status (Neither in Education, Employment nor Training) [1][2][3][4][5][6][7][8][9][10][11][12][13][14], which may be due to a negative effect of depressive symptoms on the level of energy, concentration and motivation [4]. Also, poor labour market participation may affect mental health negatively [6,14].…”
Section: Introductionmentioning
confidence: 99%